2008
DOI: 10.1017/s0265021508004638
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine vs. levobupivacaine combined with sufentanil for epidural analgesia after lung surgery

Abstract: Equivalent volumes of ropivacaine (0.2% w/v) and levobupivacaine (0.125% w/v) provided similar static and dynamic analgesia with similar incidence of minor side-effects after thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
2
3
0
2
Order By: Relevance
“…The recommended doses of propofol for induction dose(ID) and maintenance dose(MD)of anesthesia are 1-2.5 mg/kg and 50-150 μg/kg/min, respectively. [19,22,29,30] In this study, IDs of both groups for propofol OCTOBER 2015 176 PAIN A RI were established compatible with these mentioned limits. However propofol ID was found significantly low in group E. Besides, propofol anesthesia MDs in group C was established in mentioned limits but found significantly higher than that in group E. In Group E, propofol MD was found to be significantly lower than recommended dose interval.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The recommended doses of propofol for induction dose(ID) and maintenance dose(MD)of anesthesia are 1-2.5 mg/kg and 50-150 μg/kg/min, respectively. [19,22,29,30] In this study, IDs of both groups for propofol OCTOBER 2015 176 PAIN A RI were established compatible with these mentioned limits. However propofol ID was found significantly low in group E. Besides, propofol anesthesia MDs in group C was established in mentioned limits but found significantly higher than that in group E. In Group E, propofol MD was found to be significantly lower than recommended dose interval.…”
Section: Discussionsupporting
confidence: 65%
“…[8][9][10] TIVA is well documented with regard to effect, tolerability and safety. [11][12][13][14] Combination of epidural and general anesthesia is proposed to be associated with more rapid recovery, [15,16] reduced blood loss, [17] reduced risk of venous thrombosis, [18] early mobilization of the patient [19,20] and shortened stay in intensive care units. [19,21,22] The bispectral index score (BIS) has been proven to correlate well with the hypnotic state of the patient during both inhaled and IV anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Paraskevi et al 6 reported nausea, prurutis which is not statistically significant between three groups similar to the present study. Decosmo et al, 7 observed minor side effects with similar incidence among Ropivacaine with sufentanil and levobupivacaine with sufentanil similar to the present study.…”
Section: Complicationssupporting
confidence: 91%
“…A study was conducted by De Cosmo et.al comparing epidural analgesia after lung surgery. 15 In the study Ropivacaine 0.2% was compared with 0.125% Levo-Bupivacaine combined with sufentanil. They concluded that equivalent volumes of Ropivacaine 0.2% w/v and Levo-Bupivacaine 0.125% w/v provided similar static and dynamic analgesia with similar incidence of minor side effects after thoracotomy.…”
Section: Discussionmentioning
confidence: 99%